1947
DOI: 10.1177/003591574704001216
|View full text |Cite
|
Sign up to set email alerts
|

Dental Investigations of Greenland Eskimos.[Summary.]

Abstract: Prognosis: The opening of these cysts allows rapid growth of new bone to take place and the cavity fills in; this has already happened in this case after six months.The patient will be kept under careful observation; any sign of activity in the two unopened cysts will indicate surgical interference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
32
0
1

Year Published

1966
1966
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 0 publications
3
32
0
1
Order By: Relevance
“…As already mentioned, dental calculus can be the result of the ingestion of animal protein, and consequently the production of urea (Ford, 2009;Pedersen, 1947). However, other dietary sources of calcium, phosphate and potassium could also have promoted the steady increase in calculus deposition (Poff et al, 1997) from the Pre-Tiwanaku to the Post-Tiwanaku period (Llagostera, 2004;Lynch, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, dental calculus can be the result of the ingestion of animal protein, and consequently the production of urea (Ford, 2009;Pedersen, 1947). However, other dietary sources of calcium, phosphate and potassium could also have promoted the steady increase in calculus deposition (Poff et al, 1997) from the Pre-Tiwanaku to the Post-Tiwanaku period (Llagostera, 2004;Lynch, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For sample sizes, see Table 1. For explanation of plot symbols, see objects such as a bow drill (de Poncins, 1941;Pedersen, 1947;Mayhall, 1972). 2.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it seems likely that their diet of predominantly meat and fat would not have been as abrasive as many vegetable food stuffs even though eating frozen or sun-dried meat might have required vigorous chewing (Waugh, 1937;Pedersen, 1947;Davies and Pedersen, 1955). Merbs (1983: 147) observed that the anterior teeth were used to tightly grasp a piece of meat while it is sliced by a knife, and ''a bite sized morsel is cut off and swallowed after little or no mastication.''…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one in 25 adult females living in the more primitive communities of West Greenland were affected by dental caries, while one in two adult females living in communities adjacent to trading stations were affected. 5 15, 1965. rates have been reported in Alaska and elsewhere by Russell.7 Dental caries has affected almost 100 per cent of the populations in the United States and in most of the countries of Europe, and there has been consistent evidence that the prevalence of dental caries has been increasing. 8' 9 In 1936, Mountin and Townsend'0 reported observations of dental defects in American Indians in 24 reservations.…”
mentioning
confidence: 99%